Method Validation of Chloramphenicol Analysis in the Shrimp Based on Diazotization Reaction - Abdul Wafi; Ganden Supriyanto; Tjitjik Srie Tjahjandarie (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
A simple, rapid and precise spectrophotometric method has been developed and validated for the determination of Chloramphenicol (CAP) in the shrimp based on diazotization reaction at room temperature. The CAP was reduced by zinc powder and the diazotization reaction was carried out in the presence of NaNO2, bismuth nitrate pentahydrate as catalyst. The 2-napthol used as coupling agent to form a red-violet solution and the absorbance of azo dye solution was measured by UV-Vis spectrophotometer at 554 nm. The method validation parameters including linearity, accuracy, precision, limit of detection (LOD) and limit of quantification (LOQ) have been investigated. The correlation coefficient (R2) was 0.996 for concentration range 0.70 – 4.65 µg/mL. The LOD and LOQ were 0.36 µg/mL and 1.19 µg/mL. Accuracy and precision of the method were performed by spiking of CAP in the shrimp sample at concentration 1.16; 2.33; 3.49 µg/mL. Analysis result showed that the accuracy and precision of the method were 92.77-97.37 % and 0.21-2.39 % respectively.Keywords : Chloramphenicol, diazotization, shrimp, spectrophotometry, method validation.